Peer coaching - Pojkarová, Kateřina (University of Pardubice, 2018)
There are many professional coaches that help people in many areas in their life. In some companies they think of coaching as a benefit for their employments. Professional coaches are quite expensive and that could be reason for not using this “method”. Nowadays, there is another option, which is peer coaching. It means coaching in not so professional way, but in more friendly and familiar way. This paper will describe what peer coaching is, the benefits of it and it will give some advices how it could start, even in transport company.
Keywords: peer coaching